Pengujian Nomor-nomor Harapan Padi Tahan Al dan pH Rendah Hasil Seleksi In Vitro dengan Kultur Hara - Ragapadmi Purnamaningsih; Ika Mariska (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2008)
Rice productivity in acid soil is very low because of low pH,low availability of N, P, K, Ca, Mg, Mo, toxicity of Al and Mn.Development of Al tolerant varieties could increase riceproductivity in acid soil. Somaclonal variation and in vitroselection method can be used to develop new Al tolerancevarieties. A rapid screening method is needed to select alarge number of new genotypes or new inbred lines in plantbreeding, such as solution culture methods to evalu-ate Altolerantrice. This methods was used to know the responseto Al in the seedling stage, root development, and pHchanging. In this experiment solution culture method wasused to evaluate the new genotypes derived from somaclonalvariation and in vitro selection methods. These newgenotypes have been tested the tolerance characteristic byusing AlCl36H2O at 6 concentrations (0, 100, 200, 300, 400,and 500 ppm). Yoshida solution with two Al concentrationwere used to tested these genotypes. Measurement of Altolerance was based on root development by using RelativeRoot Length (RRL), the relativity of root length at 45 ppm and0 ppm. Almost all of the genotypes have RRLs higher than0.7, which means that there was a positive correlationbetween the in vitro method and solution culture method. Inthis experiment pH changes were not applicable to measurethe tolerance of the rice genotypes to Al and low pH.